2019
DOI: 10.1021/acs.cgd.9b00452
|View full text |Cite
|
Sign up to set email alerts
|

Household Aluminum Products as Insoluble Precursors for Directed Growth of Metal–Organic Frameworks

Abstract: Converting unconventional precursors into advanced separation materials can reduce manufacturing complexity while affording economic and environmental benefits. Here we report the conversion of various aluminum-containing commercial products, such as recycled beverage cans and aluminum foil, to both supported and nonsupported metal−organic frameworks (MOFs). Supported MOF/aluminum composites grow from and on aluminum via hydrothermal treatment to create multiple supported MOF topologies. The same precursor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…N-CuO/Cu composites possessed a competitively high TOF value of 1.17 × 10 −3 s −1 at 393 K, which was 1−2 orders of magnitude higher than CuO (6.99 × 10 −5 s −1 ) and superior to most reported MOF-based catalysts (Table S2). In sharp contrast, the lowest apparent activation energy (36 toward CO oxidation was observed for N-CuO/Cu (Figure 7e). A catalyst derived from CuBTC-MeIM(rt) was also fabricated for CO oxidation, and N-CuO T /Cu also exhibited high performance.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…N-CuO/Cu composites possessed a competitively high TOF value of 1.17 × 10 −3 s −1 at 393 K, which was 1−2 orders of magnitude higher than CuO (6.99 × 10 −5 s −1 ) and superior to most reported MOF-based catalysts (Table S2). In sharp contrast, the lowest apparent activation energy (36 toward CO oxidation was observed for N-CuO/Cu (Figure 7e). A catalyst derived from CuBTC-MeIM(rt) was also fabricated for CO oxidation, and N-CuO T /Cu also exhibited high performance.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, the introduction of a second ligand into the original MOFs may cause severe collapse of the intrinsic morphology. Comparatively, the heterogeneous nucleation strategy with insoluble metal precursors such as metal oxides and metal hydroxides would provide a more flexible and cost-effective route for MOF production and offer an efficient route for direction- and shape-controlled synthesis. Superior to traditional methods, development of a heterogeneous assembly strategy exhibits greater potential to fabricate multi-ligand MOFs for rapid transformation of derivatives with complex compositions and unique structures.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium-based MOF (MIL-53(Al)) produces high yields (83%) and is synthesized from Coca-Cola cans with a surface area of 800 m 2 g À1 , which is 30% less than the traditionally synthesized Al-based MOFs MIL-53(Al) (1140 m 2 g À1 ) because of impurities such as epoxy resin and plastic labeling. 50 The use of batteries has increased in the past few decades. Ultimately, their wastage has also increased globally.…”
Section: Hazardous Wastes Metals As a Source Of Mof Productionmentioning
confidence: 99%
“…The price difference is too high between commercial and waste obtained MOF, thus showing the cost-effectiveness of this method. 50 MOF-5 prepared from batteries for Zn source is priced at 42.1 $ per kg. Similarly the cost of Cu-BDC, both metal and organic linkers obtained from recycling from waste, is about 30 000 RMB per kg for conventional synthesis method, but that of the commercial one is too high.…”
Section: Benefits and Drawbacks Of Waste To Mof Synthesismentioning
confidence: 99%
“…Indeed, the use of recyclable waste as a supply for both organic and inorganic constituents offer a promising practice for the sustainable and low-cost production of high-value materials, including MOFs and MOF-composites [ 65 ], meeting at once the concepts of circular economy [ 66 , 67 ]. Recently, various significant studies of waste-derived MOFs and MOFs composites have been reported and reviewed [ 68–71 ]. This review mainly focuses on the use of PET wastes as a valuable source of ligands for MOFs production, highlighting that the PET-derived MOFs feature similar properties and adsorption performances when compared to MOFs produced with commercial organic ligands.…”
Section: Introductionmentioning
confidence: 99%